Contamination of heavy metals in birds from Embalse La Florida (San Luis, Argentina) - Cid, Fabricio Damian (2009)
Embalse La Florida is an artificial lake located in midwestern Argentina's San Luis province. It provides drinking water to ∼70% of the province's human population and ∼20% of the province is irrigated with water from the reservoir. The presence of heavy metals in Embalse La Florida's water has previously been reported. Nevertheless, no information about the levels of these contaminants in birds is available for this region. The aim of this study, therefore, is to (1) establish baseline data on lead (Pb) and cadmium (Cd) levels in birds from Embalse La Florida, (2) assess metal accumulation patterns between organs and bird species, and (3) evaluate the potential risk that these heavy metals pose for the local avifauna. We measured Pb and Cd in bone, pectoralis muscle, liver, gonad, and brain of three bird species representative of the Embalse La Florida ecosystem: Podiceps major (Great Grebe), Phalacrocorax brasilianus (Neotropic Cormorant), both of which are piscivorous, and Pitangus sulphuratus (Great Kiskadee), which is omnivorous. We also measured both heavy metals in Great Grebe eggs. Pb and Cd were detected in all of the tissues we assayed, and Pb concentrations were significantly higher than those for Cd in all tissues. The patterns of Pb and Cd accumulation differed between tissues, however. In general, gonads had the highest concentrations of Pb while Cd tended to accumulate in the liver. An interspecific analysis revealed that the omnivorous species had higher levels of both metals in bone, liver, and brain compared to both piscivorous species. There were no differences in Pb and Cd concentrations between males and females. The highest liver level of Pb (4.69 ppm wet weight) detected in Great Kiskadee, was comparable to those associated with toxic effects in birds, and Pb concentrations found in the liver of two females and two males (2.07 to 2.32 ppm wet weight) were also similar to those that could be physiologically detrimental in other species. In all birds assayed, Cd levels in liver tissue were lower than those typically shown to be harmful. Our results indicate that Great Kiskadees are highly polluted by Pb and their exposure to this contaminant exceeds the level reported to trigger adverse effects. This is the first study to assay heavy metals in birds from midwest Argentina and provides a starting point for studies examining the impact that these metals have on both wildlife and humans in the region.